Cephalic cutaneous allodynia in children and adolescents with migraine of short duration: A retrospective cohort study. (January 2019) - Levinsky, Yoel; Zeharia, Avraham; Eidlitz-Markus, Tal
Background: Allodynia is prevalent in adults with migraine and has been associated with long disease duration and severe course. Studies of the pediatric population are sparse. The aim of this study was to evaluate the rate of cephalic cutaneous allodynia in children and adolescents within the first 6 months of migraine onset and to identify associated clinical and migraine-related parameters. Methods: The electronic database of a tertiary pediatric headache clinic from 2014 to 2017 was retrospectively searched for all children and adolescents diagnosed with migraine headache within 6 months or less of symptom onset. Cephalic cutaneous allodynia was identified by validated questionnaire. Demographics, symptoms, and headache-related parameters were compared between patients with and without allodynia. Results: The cohort included 119 patients, 69 girls (58.0%) and 50 (42.0%) boys, of mean age 11.6 ± 3.6 years. Mean time since onset of migraine disease was 3.6 ± 1.8 months. Cephalic cutaneous allodynia was reported by 31.1% of patients. It was significantly associated with female gender ( p  = 0.03), older age at admission ( p  = 0.037), older age at onset ( p  = 0.042) migraine with aura ( p  = 0.002), and higher rate of awakening pain ( p  = 0.017). Conclusions: Cephalic cutaneous allodynia may occur in children and adolescents already in the first 6 months of migraine onset. Contrary to adult studies, we found no association of allodynia with migraine frequency or long disease duration. Allodynia was significantly associated with migraine with aura, female gender, and awakening pain. A genetic tendency may contribute to the appearance of allodynia in the pediatric age group.